(untitled) (Research, Society and Development, 2021)
This study aims to inform about the execution of a study that investigates how the implementation of Permanent Education in the multidisciplinary team working in the Regulation Center can contribute to the regulatory process of the SUS in a city in Rio de Janeiro. Thus, it proposes the collective construction of educational strategies in order to reorganize the work process in this sector. The research will be a descriptive and exploratory study method, with a qualitative approach, of the Convergent Assistance type of research, seeking to articulate practical and academic knowledge. Data collection will be divided into two stages: the first will be developed through a semi-structured questionnaire in order to stimulate reflection and discussion of the topic and generate the necessary problematization for the realization of the second stage, which will consist of meetings with the team multiprofessional through conversation circles, followed by workshops, using active methodologies. Data analysis will occur through Bardin’s content analysis in the questionnaires and later will have the conversation circles and workshops analyzed based on the Arco de Maguerez, both in line with the National Policy for Continuing Education and inspired by the theorist Paulo Freire, considering the problems arising from everyday life and the subject’s relationship with educational work. It is envisioned that professionals working in the Regulation Center are able to grasp their role as authors in the search for processes of change and improvements in the reality experienced, providing effective user access to SUS health services.